Fluctuating ionic polarizabilities in the condensed phase: first-principles calculations of the Raman spectra of ionic melts - Heaton, R; Madden, P (2008)
An approach to calculating Raman spectra of ionic materials from first principles is described; the method is applicable to molten systems which cannot be treated by summing the contributions from normal modes of vibration. The approach offers a way to validate a simulation by comparison with a Raman spectrum; for many materials under extreme conditions of temperature or pressure, Raman spectroscopy may be the only practicable experimental window on the structure at the atomic scale. The method involves the direct calculation of the time correlation functions of the polarizability fluctuations in the sample, which involves the introduction of a model for the dependence of the polarizability on the ionic coordinates. The model is parameterized by fitting a large number of values of the polarizabilities of individual ions in condensed phase environments. These are calculated, using a recently introduced ab initio method, from the response of the electron density to an applied electric field on a series of configurations obtained from molecular dynamics simulations of the material of interest. The results of the calculations are compared with experimental spectra on liquid and solid LiF, liquid BeF2, and LiF:BeF2 mixtures. The spectra are well reproduced by the method, particularly the isotropic components which are generally most useful for diagnosing coordination structures in experimental studies. Since the ab initio methodology has already been shown to work for oxides, the method should be applicable to melts of geophysical interest inter alia.